An Approach to the Patients with Cryopyrin-associated Periodic Syndrome (CAPS) : a New Biologic Response Modifier, Canakinumab - YOKOTA, Shumpei; KANETAKA, Taichi; MORI, Masa-aki; HEIKE, Toshio; IMAGAWA, Tomoyuki; NOZAWA, Tomo; KIKUCHI, Masako; KIZAWA, Toshiatsu; MIYAMAE, Takako; NISHIKOMORI, Ryohta; TAKATA, Hidetoshi; HARA, Toshiro (Japanese Journal of Clinical Immunology, 2012)
Cryopyrin-associated periodic syndrome (CAPS) comprises a group of rare, but severe, autoinflammatory syndrome, and includes 3 distinct conditions, familial cold autoinflammatory syndrome (FCAS), Muckle-Wells syndrome (MWS), and neonatal-onset multisystem inflammatory disease (MONID). These syndromes are characterized by urticarial-like rash, periodic fever, central nervous system inflammation, an arthropathy, and the risk of amyloidosis. About 20% die by age 20 years in the most severe cases. The disease is associated with mutations in the NLRP3 gene that encodes for the protein cryopyrin, a component of the inflammasome complex that regulates the production and secretion of IL-1β. Canakinumab is a human IgG monoclonal antibody targeting IL-1β. The clinical trials of canakinumab for patients with CAPS in both western countries and Japan were well-tolerated in most patients, and provided significant advantages over existing competitive therapies. Although no serious adverse effects have been reported, the frequencies of common infectious diseases including nasopharyngitis, upper respiratory tract infections, and gastroenteritis were reported presumably due to the blockade of proinflammatory cytokine, IL-1β. For us pediatrician, it will be important to be more careful for infectious diseases to provide the maximum safety of canakinumab for these patients.